PSYCHOLOGICAL FEATURES OF NORMATIVE REGULATION OF THE POLICE OFFICERS’ CONDUCT OF THE NATIONAL POLICE OF UKRAINE - Кудерміна, О. І.; Лісун, С. Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article analyzes the psychological characteristics of normative regulation of the police officers’ conduct of the National Police of Ukraine. The adopted to discuss the authors attempted to examine the system of normative regulation of human behavior, the concept of social rules and the group norms. In the course of theoretical study the authors concluded that regulation of police officer’s conduct is carried out by a complex interaction of social norms (relevant to the specific historical period of its existence) and hierarchical system of personal values ​​(typical for the law enforcement officer). The way of forming of socially expected system of police officers’ normative regulation of the National Police of Ukraine - is a long and complex process of transformation of the legal principles of activity, group norms of the police officers’ conduct and modification of proclaimed norms of activity into personal norms of human behavior that carries out law enforcement functions